Seeking emergency contraception in the United States: A review of access and barriers. Issue 4 (21st April 2019) - Moore, Alia; Ryan, Sarah; Stamm, Carol
ABSTRACT: Federal regulations governing access to levonorgestrel (LNG) emergency contraception (EC) have evolved since its introduction in the 1990s. LNG EC was initially available by prescription only, but is now available over-the-counter to consumers of all ages. Nonetheless, consumers seeking EC in their communities may face ongoing barriers to access, including low stock and inaccurate information provided by pharmacy staff. We conducted a review of LNG EC secret shopper studies to describe changes in EC access and barriers over time. EC access was compared across all applicable studies, which were published during 2003–2016. When possible, reasons for EC unavailability, helpfulness of pharmacy staff when EC was not in stock, and accuracy of EC information provided by pharmacy staff were described. Overall, access to EC appeared to be improving. However, EC was unavailable during 31 percent of encounters. Pharmacy staff attributed this to "low demand" (30 percent) or EC being "out of stock" (21 percent). Personal objections (9 percent) and store policy (10 percent) were also cited in studies from earlier years. Inaccurate information provided by pharmacy staff persists regarding federal EC regulations, mechanism of action, and drug administration. Pharmacy staff should remain informed about EC and its regulations in order to reduce remaining access barriers.